2006
DOI: 10.1111/j.1398-9995.2006.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of asthma control: an economic appraisal of the GOAL study

Abstract: Background:  The Gaining Optimal Asthma ControL (GOAL) study has shown the superiority of a combination of salmeterol/fluticasone propionate (SFC) compared with fluticasone propionate alone (FP) in terms of improving guideline defined asthma control. Methods:  Clinical and economic data were taken from the GOAL study, supplemented with data on health related quality of life, in order to estimate the cost per quality adjusted life year (QALY) results for each of three strata (previously corticosteroid‐free, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 10 publications
4
77
0
1
Order By: Relevance
“…Seven studies compared combination vs combination (37,43,48,50,52,54,59). Seven additional studies compared combination vs monotherapy (36,40,44,49,53,55,61). Eight studies compared monotherapy vs monotherapy (38,41,42,45,46,51,56,58).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies compared combination vs combination (37,43,48,50,52,54,59). Seven additional studies compared combination vs monotherapy (36,40,44,49,53,55,61). Eight studies compared monotherapy vs monotherapy (38,41,42,45,46,51,56,58).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Clinical treatment guidelines such as GINA and recent trial based cost-effectiveness models like the Briggs et al CEA of the Gaining Optimal Asthma Control (GOAL) study (61) have shifted away from an emphasis on lung function or SFD and moved towards a focus on achieving or maintaining control. These reasons along with the lack of quality for primary outcome measures used in the reviewed studies (22.5% of studies had appropriate outcome measures per QHES item 10), supports the need to develop new asthma simulation models that include comprehensive measures like asthma control in the structure (e.g.…”
Section: Health Economic Recommendations (Past and Present)mentioning
confidence: 99%
“…Results allow a utility (decrement) to be attached to clinical events, and provide a coefficient (mediated by clinical events) which captures utility differences by trial arm. Briggs et al [41] demonstrated that for an RCT where no significant difference in utility was observed using a traditional approach, event-based methods resulted in a moderately significant difference between treatment groups. This approach is more closely aligned with model-based economic evaluations, where utilities are typically attached to health states.…”
Section: Choice Of Outcome Measurementioning
confidence: 99%
“…But these considerations are largely hypothetic and need to be confronted to results of formal cost-effectiveness studies. In the economic analysis of the GOAL study, increasing the proportion of total asthma control was associated with significant gains in quality-adjusted life years, but the corresponding increase in treatment costs was not fully compensated by the reduction in healthcare utilization (23). Another way of determining which level of control has to be achieved is to assess the relationship between control and quality of life; both types of indices usually correlate well with each other (24,25).…”
Section: Control Of Asthma: What Is the Target?mentioning
confidence: 99%